TRANSACTIONAL PEACE WITHOUT RECONCILIATION: A DIALECTICAL ANALYSIS OF POWER IN TRUMP’S ISRAEL–PALESTINE (HAMAS) PEACE PLAN - Rohman, Syaiful; Hawadi, Lydia Freyani; Bulgini, Moh. Iqbal, IB (UI Scholars Hub, 2025)
Abstract The Israel– Palestine (Hamas) conflict in the Gaza Strip has persisted for decades, marked by cyclical violence and chronic diplomatic stalemate. One of the latest attempts to end this enduring conflict emerged from the initiative of U.S. President Donald J. Trump through the so-called “20-Point Gaza Peace Plan,” which was claimed to offer a comprehensive solution. However, this approach has been widely criticized for its transactional nature, perceived bias, and neglect of the historical and existential complexities underlying the conflict. This article aims to critically analyze Trump’s peace initiative through the philosophical framework of Georg Wilhelm Friedrich Hegel (1807), particularly his concepts of Anerkennung (mutual recognition) and the Master–Slave dialectic, in order to evaluate whether the plan could lead to sustainable peace or merely reinforce existing structures of domination. Employing a qualitative approach with literature study and philosophical discourse analysis, this research draws on primary sources such as official documents of Trump’s peace plan, international institutional reports, and secondary literature on Hegelian thought and its application in conflict and international politics. The analysis reveals that, while Trump’s peace plan functions as an antithesis that disrupts the prevailing status quo, it fails to produce a reconciliatory synthesis because it does not address the core of the conflict: the absence of existential recognition between Israel and Hamas. The plan reproduces an asymmetric power relationship, positioning Israel as the hegemonic “Master” and Palestine as the subordinated “Slave,” whose sovereignty is both limited and conditional. Without mutual recognition as equal political subjects, the proposed peace remains a temporary ceasefire vulnerable to collapse. Keywords: Hegelian Dialectics, Anerkennung, 20-Point Gaza Peace Plan, Israel–Hamas Conflict, Power Relations